New synonymies of Coprophilus (Zonyptilus) pentatoma Fauvel, 1897 (Coleoptera: Staphylinidae: Oxytelinae) - Gildenkov, Mikhail Yu. (Zootaxa, 2017)
The following new synonymies are established: Coprophilus (Zonyptilus) pentatoma Fauvel, 1897 = C. (Z.) longicornis Bernhauer, 1903, syn. n. = C. (Z.) bimaculatus Luze, 1904, syn. n. = C. (Z.) rufitarsis Kashcheev, 1999, syn. n.